Replacement of corn with mango meal for dairy goats - Silva, Janaina de L.; Guim, Adriana; Carvalho, Francisco F. R. de; Mattos, Carla W.; Menezes, Daniel R.; Coelho, Maria Claudia S. C.; Garcia, Diogo A. [UNESP]; Pereira Neto, Jose D.; Soares, Luciana F. P. (Univ Antioquia, Fac Ciencias Agrarias, 2016)
Background: the high volume of mangos harvested during the season, associated with inappropriate management of the fruit after harvesting results in increased waste of this valuable resource. Mango fruit, rich in carbohydrates, has potential use in animal feeding. Objective: to evaluate the effect of replacing corn with whole mango meal (0, 330, 660, and 1000 g/Kg on dry matter basis) in the diets of dairy goats on rumen fermentation kinetics, intake, milk yield and composition, and economic results. Methods: eight lactating Saanen crossbred goats (48.7 +/- 1.99 Kg body weight) were used in the experiment, which started 48 days postpartum and lasted until completing 124 days of lactation. The experimental design consisted of a double Latin square (4x4) with four treatments, four periods and four animals per square. Results: a reduction (p<0.05) was observed in gas production from total carbohydrates and fiber carbohydrates. Replacement of corn with whole mango meal showed no effect on DM intake (1,890 g/d), crude protein (278 g/d) and neutral detergent fiber (959 g/d). Milk production (4% fat-corrected) and milk composition were not affected by the treatments, except for fat and myristoleic fatty acid contents. The economic evaluation showed a reduction in the total feeding cost and a better benefit: cost ratio. Conclusion: whole mango meal can replace corn up to 330 g/Kg in the diet of lactating goats.
Keywords: economic evaluation; fatty acids; food waste; in vitro gas production